Flexibilidade na arquitetura escolar: a experiência dos edifícios-tapete no Recife (PE) na década de 1970 - Larissa Morgana Leão Silva de Sousa (2023)
Flexibility in architecture consists of a building's potential to easily adapt, accommodating both internal and external changes. This feature was especially explored during the modern period, in response to challenges such as post-war minimal housing and the novelty of standardization and industrialization of construction components. This led to a production characterized by experimentation and the creative freedom of architects, despite frequent rigidity and technical control, which would later be critiqued in the revision of modern architecture. This research focuses on the application of flexibility in school architecture, driven by the contemporary challenge of the obsolescence of school structures. It is structured as a case study, delving into the production of mat-buildings in Pernambuco in the 1970s, following the concept created by architect Alison Smithson for extensible buildings structured in grids. Its objective is to relate the experience of the Metropolitan Region of Recife to the theory of flexibility and indeterminacy in modern architecture. It is adopted a descriptive methodology, starting with a literature review to associate episodes of flexibility in modern architecture with relevant architectural designs to observe the resources employed in different instances. The research also investigates the relationships between educational policies and school architecture in modern Brazil, delving into Pernambuco's production for design analysis and evaluations of the listed schools. Through this, it confirms the relevance of the theme of flexibility in school architecture and the need for further exploration through architectural research.